Membrane Technology for Water Pollution Control: A Review of Recent Hybrid Mechanism - Martini, Sri (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Current development of membrane technology for purifying polluted water and wastewater is discussed in this review in accordance with its hybrid application with other types of water treatment methods such as adsorption, advanced oxidation processes (AOPs), and biological activated sludge. This hybrid implementation aims are to lengthen membrane lifespan and elude severe fouling on the surface and pore of the membrane. Membrane material and fabrication technology were concisely included. Two prominent materials to fabricate membrane namely polymeric and ceramic are reviewed well along with the exploration of biopolymers based-materials such as starch and alginate. Several fabrication methods available to be implemented in research or industrial large scale including interfacial polymerization technique, non-solvent induced phase separation, temperature induced phase separation, electrospinning, and sintering are deliberately discussed. The next section includes fouling analysis involving reliable fouling mechanism namely Hermias models to help with the explanation of fouling occurrence during filtration. These models covers four different mechanisms namely complete blocking, standard blocking, intermediate blocking, and cake filtration models. Ultimately, recent research reporting the outcome of the hybridization of membrane and adsorption, biosorption, coagulation-flocculation, AOPs, and biological treatment using microorganism were properly reviewed. Overall, this review considerably promotes the findings of those works which mostly revealed positive outcome of the hybrid membrane system contributing to stronger foundation for future research.